Complex adaptive leadership : embracing paradox and uncertainty - Obolensky, Nick (Gower, 2010)
We all seem intuitively to know leadership 'isn't what it used to be' but we still cling to old assumptions which look anachronistic in changing and challenging times. Organisations and their contexts are increasingly paradoxical and uncertain. A broader approach to leadership is needed. Nick Obolensky has practiced leadership in the public, private and voluntary sectors. He has also researched it, and taught it over many years in leading business schools. In this exciting book he brings together his knowledge of theory, his own experience, and the results of 15 years of research.- Resumé vydavatel
Keywords: řídící práce; organizační chování; management; leadership; organizational behavior; elektronické knihy; příručky; electronic books; handbooks and manuals